Leaders make the future: Ten new leadership skills for an uncertain world - Johansen, Bob; Ryan, John R. (San Francisco B K Business Book, 2012)
Identifies surprising new leadership skills vital to coping with today?s uncertain, rapidly changing world Includes exercises and assessments for developing and applying these skills A fully updated and revised edition of a book adopted by leaders at Procter & Gamble, Target, McDonalds, Electronic Arts, UPS, Kraft, and many other companies We are in a time of disruptive change?traditional leadership skills won?t be enough, noted futurist Bob Johansen argues.